1995
DOI: 10.1002/j.1460-2075.1995.tb07292.x
|View full text |Cite
|
Sign up to set email alerts
|

The 3′-terminal region of the mRNAs for VSG and procyclin can confer stage specificity to gene expression in Trypanosoma brucei.

Abstract: The variant surface glycoprotein (VSG) and procyclin are the respective major surface antigens of the bloodstream and the procyclic forms of Trypanosoma brucei. These proteins and their mRNAs are both the most abundant and absolutely characteristic of their respective life cycle stages. We show that the 3'-terminal region of these mRNAs regulates expression of a reporter gene in an inverse manner, depending on the developmental form of the parasite. In the case of VSG mRNA, the 97 nt sequence upstream from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
86
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 52 publications
2
86
0
Order By: Relevance
“…The transcriptional machinery in trypanosomes is unusual as genes are transcribed as polycistronic precursor mRNAs that are subsequently processed by trans-splicing and polyadenylation (59,60). No polymerase II promoters or transcription factors that might interact with them have been identified in trypanosomes to date, but a major regulatory mechanism for control of gene expression occurs at the posttranscriptional level through mRNA stability (48,61,62). Many CDK complexes have been shown to be involved in transcriptional regulation in yeast and higher eukaryotes (24, 64 -66).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional machinery in trypanosomes is unusual as genes are transcribed as polycistronic precursor mRNAs that are subsequently processed by trans-splicing and polyadenylation (59,60). No polymerase II promoters or transcription factors that might interact with them have been identified in trypanosomes to date, but a major regulatory mechanism for control of gene expression occurs at the posttranscriptional level through mRNA stability (48,61,62). Many CDK complexes have been shown to be involved in transcriptional regulation in yeast and higher eukaryotes (24, 64 -66).…”
Section: Discussionmentioning
confidence: 99%
“…Cisacting factors that affect mRNA stability have been identified within the 3Ј-untranslated region (UTR) 1 of specific transcripts. AU-rich cis-regulatory elements present in the 3Ј-UTR have been shown to regulate the stability of transcripts of procyclic acidic repetitive proteins (EP and GPEET) or procyclins (6,7) and the variable surface glycoprotein gene transcripts in Trypanosoma brucei (2,8) and those of mucin (9), amastin (10), and H2A histone (11) genes in Trypanosoma cruzi. Trans-acting factor, a developmentally regulated U-rich RNA-binding protein involved in selective mRNA destabilization, has recently been identified in T. cruzi (12).…”
mentioning
confidence: 99%
“…However, Northern blots showed that the GP63 mRNAs accumulate to a detectable steady-state level only in bloodstream trypanosomes, as do VSG mRNAs. In the case of VSG mRNAs, their semiconserved 3Ј-UTRs are important in conferring the bloodstream stage specificity to the VSG mRNAs (64). A multiple alignment of the three 3Ј-UTRs of the sequenced trypanosome GP63 genes revealed a high level of homology in those regions.…”
Section: Discussionmentioning
confidence: 99%
“…Our attempts to identify substantive sequence similarities in the 3Ј-UTR sequences of several expressed VSG genes and these three GP63 3Ј-UTRs were not particularly revealing; however, a sequence resemblance to a 14-mer element conserved in all VSG mRNAs was observed immediately upstream of the polyadenylation site of the GP63 genes. The presence of this 14-mer element has been shown to be necessary, but not sufficient, for VSG gene regulation (64).…”
Section: Discussionmentioning
confidence: 99%